The Apocryphal Gospels of Mary in Anglo-Saxon England. - Clayton, Mary (Cambridge studies in Anglo-Saxon England., 1999)
This book presents editions, with facing translations and commentary, of three long-neglected Old English apocryphal gospels dealing with the birth, childhood, death and assumption of Mary, extant in Anglo-Saxon manuscripts. An extensive introduction covers the origins and development of the apocrypha and their influence in Anglo-Saxon England.